Reconstructing Wage Justice for Fixed-Term Workers in Indonesia: Integrating Ijarah ‘ala al-‘Amal and Labor Law - Nurul Chairi; Siti Sonya Nadzilla; Fahmi Makraja (Jurnal Ilmiah Guru Madrasah, 2026)
Fixed-term employment provides employers with flexibility in organizing labor but continues to raise legal questions concerning wage adequacy, employment security, and continuity of worker protection. This article examines the legal construction of wages and protection for workers employed under Perjanjian Kerja Waktu Tertentu (PKWT) in Indonesia, evaluates its compatibility with ijarah ‘ala al-‘amal and maqasid al-shari‘ah, and develops a normative reconstruction of wage justice. The study employed normative legal research using statutory, conceptual, case, and comparative-normative approaches. Legal materials were analyzed doctrinally through grammatical, systematic, and teleological interpretation, legal syllogism, and six indicators of wage justice: contractual clarity, adequacy, proportionality, timely payment, protection against unjustified differentiation, and continuity of socioeconomic protection. The analysis demonstrates that Indonesian labor law restricts PKWT to legally eligible work, limits time-based PKWT and any extension to a maximum total period of five years, requires reclassification as indefinite-term employment when PKWT is used for legally ineligible or permanent work, and guarantees wages, end-of-contract compensation, and social security. Indonesian labor law and ijarah ‘ala al-‘amal substantially converge in requiring clear contractual terms, proportional remuneration, timely payment, and protection of workers’ economic rights. Their compatibility remains incomplete, however, when contractual consent masks unequal bargaining power, minimum-wage compliance does not ensure an adequate livelihood, or compensation fails to provide continuity of protection. Wage justice should therefore be reconstructed through substantive wage determination, protection against differentiation based solely on contractual status, transparent wage provisions, automatic compensation and continuous social protection, and effective supervision and remedies.